2022
DOI: 10.3389/fimmu.2022.900119
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Successful Immunotherapy Improved the Prognosis of the Unfavorable Subset of Cancer of Unknown Primary

Abstract: BackgroundCancer of unknown primary (CUP) is heterogeneous and has a wide variety of clinical presentations and a poor prognosis in most patients, with a median overall survival of only 6 months. The development of molecular profiling contributes to precision therapy, and targeted drugs and immune checkpoint inhibitors (ICIs) greatly promote individualized treatment.Case presentationHere, we reported a case of an unfavorable subset of CUP who had a long time of survival after the immunotherapy-prominent compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…One-third of the cases in the NivoCUP-2 trial had a PD-L1 TPS ≥ 1% ( 38 ). A recent case report also showed that when the TMB was high, the combination of pembrolizumab and chemotherapy was effective, even in patients in ‘unfavorable prognosis’ CUP groups ( 47 ). It has been reported that viral antigens in anti-PD-1 treatment results are one of the predictive factors ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 98%
“…One-third of the cases in the NivoCUP-2 trial had a PD-L1 TPS ≥ 1% ( 38 ). A recent case report also showed that when the TMB was high, the combination of pembrolizumab and chemotherapy was effective, even in patients in ‘unfavorable prognosis’ CUP groups ( 47 ). It has been reported that viral antigens in anti-PD-1 treatment results are one of the predictive factors ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 98%
“…Однако в исследовании L. Davis et al у пациентов с новообразованиями, развившимися на фоне НФ 1-го и 2-го типа, не было обнаружено связи между экспрессией PD-L1, инфильтрацией CD8+ лимфоцитами и выживаемостью больных [9]. В настоящее время из литературы известно о четырех пациентах с ЗООПН с различными уровнями экспрессии PD-L1, у которых наблюдали полный метаболический ответ на анти-PD-1 терапию [9][10][11]. Помимо злокачественных опухолей в некоторых исследованиях приводятся данные об увеличении экспрессии PD-L1 development and prognosis of MPNSTs has not yet been determined.…”
Section: Introductionunclassified